2014
DOI: 10.1186/1471-2393-14-154
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic analysis of masseter muscle in newborns during suction in breast, bottle or cup feeding

Abstract: BackgroundWhen breastfeeding is difficult or impossible during the neonatal period, an analysis of muscle activity can help determine the best method for substituting it to promote the child’s development. The aim of this study was to analyze the electrical activity of the masseter muscle using surface electromyography during suction in term newborns by comparing breastfeeding, bottle and cup feeding.MethodsAn observational, cross-sectional analytical study was carried out on healthy, clinically stable term in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 32 publications
0
21
0
6
Order By: Relevance
“…Few studies evaluated the impact of mode of milk feeding (breast, bottle and cup) on oral muscles activities. Based on sEMG measurements, some authors showed that cup feeding as of the first weeks or months (Franca et al, 2014;Gomes et al, 2006) or bottle-feeding with a chewing-like bottle teat (Sakashita et al, 1996) could be an alternative method if the infant cannot be breastfed, because these methods provide muscle activity similar to breastfeeding. Muscle activity was also shown to change with mode of milk feeding because sucking from the bottle results in a hypo activity of the masseter and temporalis muscles and a hyper activity of the buccinator muscle (the muscle forming the anterior part of the cheek), compared to sucking from the breast (Gomes et al, 2006).…”
Section: Impact Of the Mode Of Milk Feedingmentioning
confidence: 99%
“…Few studies evaluated the impact of mode of milk feeding (breast, bottle and cup) on oral muscles activities. Based on sEMG measurements, some authors showed that cup feeding as of the first weeks or months (Franca et al, 2014;Gomes et al, 2006) or bottle-feeding with a chewing-like bottle teat (Sakashita et al, 1996) could be an alternative method if the infant cannot be breastfed, because these methods provide muscle activity similar to breastfeeding. Muscle activity was also shown to change with mode of milk feeding because sucking from the bottle results in a hypo activity of the masseter and temporalis muscles and a hyper activity of the buccinator muscle (the muscle forming the anterior part of the cheek), compared to sucking from the breast (Gomes et al, 2006).…”
Section: Impact Of the Mode Of Milk Feedingmentioning
confidence: 99%
“…With regard to Speech Therapy, improving the pattern of natural breastfeeding is fundamental, considering the bony and muscular development of the stomatognathic system, due to the intense muscular activity of the peribucal region (20,26,27) . Breastfeeding also prevents the installation of deleterious oral habits, such as the use of pacifiers and digital suction (10,28) , in addition to enabling the extension of the link (9) and the stimulation of the hearing and the language of the NB (17) .…”
Section: Discussionmentioning
confidence: 99%
“…A past study (Medeiros, Ferreira, & Felício, 2009) showed a correlation between the duration of breastfeeding and positive aspects of tongue, lip and mandible mobility, while the duration of artificial feeding correlated negatively with masticatory and speech performance in children aged 6-12 years. In addition, past studies observed that bottle-feeding does not stimulate the activity of masticatory muscles and the range of mandibular movement as breastfeeding does (França, Sousa, Aragão, & Costa, 2014;Gomes et al, 2006). Thus, harmful stimuli over long periods of time may impair orofacial functions, such as masticatory performance, influencing the child to avoid harder foods.…”
Section: Bottle-feeding and Food Consistencymentioning
confidence: 99%